Antibacterial Activities of Secondary Metabolites Derived from Streptomyces sp. VITGV38 (MCC4869) against Selected Uropathogens - Amjad Hussain; John Godwin Christopher (Journal of Pure and Applied Microbiology, 2023)
Streptomyces sp. VITGV38 (MCC8469) was obtained from the VIT University Microbiology Laboratory where it was isolated from tomato plants. This strain was mass-cultured for 15 days and its extracellular metabolites were extracted in ethyl acetate using a liquid–liquid extraction method. The antibacterial test was performed on the ethyl acetate crude extract against selected urinary tract pathogens, Proteus mirabilis (MTCC-442), Enterococcus faecalis (MTCC-439), Klebsiella pneumoniae (MTCC-109), and Escherichia coli (MTCC-1687), The extract developed a clear inhibition zone that measured between 17–21 mm. The minimum inhibition concentration was observed from a concentration of 25 μg/ml against all selected uropathogens. GC-MS analysis revealed 35 diverse compounds in the ethyl acetate crude extract, which includes 1,2 benzenedicarboxylic acid bis(2methylpropyl) ester, dibutyl phthalate, bis (2-ethylhexyl) phthalate, didodecyl phthalate, octadecanoic acid dodecyl ester, and dodecane. These six compounds are the major antimicrobial compounds present in the ethyl acetate extract. VITGV38 showed greyish aerial mycelium. Scanning electron microscopy revealed elliptical spores with a chain-like smooth orientation.